The Constitutional Principle of Proportionality in Criminal Law - Soares, Ricardo Maurício Freire; Neto, Mario Fausto de Oliveira; Alves, Robson Cosme de Jesus (Revista Amagis Jurídica, 2024)
The present work aims to highlight the ways how the idea of proportionality of Criminal Law is capable of learning and building values and purposes of the legal order.